Nonlinear coordinated excitation and TCPS controller for transient stability enhancement in power systems - Ashfaque Ahmed Hashmani. (2008)
The research work presented deals with the design of a robust nonlinear coordinated generator excitation and TCPS controllers to enhance the transient stability of power systems.